Bonapartesaurus rionegrensis, a new hadrosaurine dinosaur from South America: implications for phylogenetic and biogeographic relations with North America - Cruzado Caballero, Penélope (2017)
The Gondwanan hadrosaurid dinosaur record is relatively poorly known and very complicated. A new hadrosaurid, Bonapartesaurus rionegrensis, gen. et sp. nov., from the late Campanian–early Maastrichtian of the Salitral Moreno site, Argentina, is characterized by the following combination of characters: the ratio between the height of the neural spines and that of the centrum of the sacral vertebrae greater than 3.5; neural spines of the anterior section of the caudal vertebrae extremely long and evenly expanding distally; a preacetabular process of the ilium slightly deflected ventrally, with the angle greater than 150°; the ratio between the maximum dorsoventral depth of the posterior end of the preacetabular process and the dorsoventral distance from the pubic peduncle to the dorsal margin of the ilium less than 0.50; the ratio between the dorsoventral height and anteroposterior length of the iliac blade 0.8 or greater; asymmetrical lateral profile of the supraacetabular process; the posterior portion of the postacetabular process markedly thicker mediolaterally as a result of the dorsomedial twist of the postacetabular process; an anteriorly expanded cnemial crest restricted to the proximal end of the tibia; and articular surface of the astragalus for the internal malleolus of the tibia moderately expanded medially, articulating with only part of the ventral surface of the tibial internal malleolus. Our phylogenetic analysis indicates that Bonapartesaurus is located within the Tribe Saurolophini. Paleobiogeographically, its presence suggests at least two saurolophine dispersal events from North America, one toward South America and another toward Asia, no later than the late Campanian. http://zoobank.org/urn:lsid:zoobank.org:pub:1ADEDB71-1FD6-4081-915D-6C73D8389408 SUPPLEMENTAL DATA—Supplemental materials are available for this article for free at www.tandfonline.com/UJVP Citation for this article: Cruzado-Caballero, P., and J. Powell. 2017. Bonapartesaurus rionegrensis, a new hadrosaurine dinosaur from South America: implications for phylogenetic and biogeographic relations with North America. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1289381.